Beyond the skin: immunological profiles and infectious complications in ALOX12B-associated autosomal recessive congenital ichthyosis - Sefer, Asena Pinar; Catak, Mehmet Cihangir; An, Isa; Keser Ozturk, Necmiye; Baykal Selcuk, Leyla; Dincer, Oguz Salih; Benamar, Mehdi; Getachew, Feven; Schmitz-Abe, Klaus; Agrawal, Pankaj B.; Bayram Catak, Feyza; Erman, Baran; et al. (Frontiers in Immunology, 2025)
BackgroundPathogenic variants in ALOX12B, a crucial enzyme involved in epidermal lipid processing, are among the most common causes of autosomal recessive congenital ichthyosis (ARCI). Although traditionally considered a cutaneous disorder, the systemic immunological implications of ALOX12B deficiency remain poorly understood.ObjectivesWe aimed to broaden the dermatologic and immunologic spectrum of ALOX12B-associated ARCI by characterizing the clinical, immunologic, and genetic features of six patients from three consanguineous families.MethodsThis prospective study included six patients with ALOX12B-associated ARCI identified through whole-exome sequencing. Detailed dermatological evaluations, infection histories, immunoglobulin profiles, lymphocyte subset analyses, and vaccine response assessments were performed.ResultsAll patients exhibited early-onset generalized ichthyosis, ranging from delayed-onset lamellar ichthyosis to collodion membrane presentations accompanied by nonbullous erythroderma. Two distinct biallelic ALOX12B variants were identified: a novel p.Thr383Lys and the known p.Cys544Arg. Several patients demonstrated recurrent bacterial or fungal infections (n = 5), markedly elevated serum IgE levels (n = 4), and isolated abnormalities in vaccine responsiveness (n = 2). Lymphocyte counts and other immunoglobulin classes were generally preserved; however, decreased IgG levels were observed in one patient (P3.1). Intravenous immunoglobulin replacement therapy reduced the frequency of infections in patients (P1.1 and P1.2).ConclusionsOur findings suggest that ALOX12B-related ARCI may involve secondary immune dysregulation, driven by chronic compromise of the epidermal barrier. An immunologic evaluation is warranted in selected cases, particularly those with a history of susceptibility to infections. Multidisciplinary care, encompassing dermatology, immunology, and genetics, is crucial for achieving optimal outcomes in ARCI.